A confidencialidade da arbitragem e o direito à informação e à fiscalização dos acionistas em companhias abertas - Toigo, Daiille Costa (2024)
The objectives of this work are to study and approach the confidentiality of arbitration and the right to information and supervision of shareholders in publicly-held companies. The topic raises many discussions, especially when it comes to publicly-held corporations, subject to the new market regime and the stipulation of an arbitration clause in their statutes. Firstly, the binding of contemporary shareholders to the insertion of a statutory arbitration clause is questioned and, notably, regarding dissident shareholders, absentees and those who join the company later, that is, after inclusion of the arbitration clause in public limited companies. The study also addresses the confidentiality that is intrinsic to the arbitration procedure and which constitutes one of its main advantages; equally, it addresses its observance in the occurrence of a material fact and the need or not for disclosure to the stock market, since this is premised on the right to information and inspection of shareholders, which may conflict with the company's social interest, as the Disclosure of some sensitive information may compromise the preservation and continuity of the company. Therefore, this study will address very controversial topics, both in doctrine and in jurisprudence, involving corporate arbitration, which are of paramount importance, but also confidentiality and the right to information and supervision of shareholders in publicly-held companies, also encompassing basic issues of the functioning of the capital market based on current Corporate Law. Initially, the history, concept, main aspects of arbitration and its advantages will be briefly discussed; the species, the applicable principles; arbitrability and its effects. Afterwards, we will delve into the specific topic of corporate arbitration, debating the insertion of the arbitration clause and the binding of shareholders (contemporary, absentee, dissident and future) and administrators, before and after the reform of the Arbitration Law, also dealing with the right to recess; the possibility of including an arbitration clause in a shareholders' agreement, including brief notes from Comparative Law on the topic. Thus, we will have support for understanding regarding the confidentiality of arbitration, the right to information and inspection of shareholders, corporate governance in the capital market, the characterization and disclosure of material facts and, as well as the binding of shareholders to the arbitration clause and the observance of confidentiality in the arbitration procedure before and after the reform of the Arbitration Law, as well as the treatment of confidentiality in various jurisdictions. Finally, a suggestion for resolving the problem addressed in this study based on the analysis of national regulations brought up here, as well as in Comparative Law